Answer:
59
Step-by-step explanation:
Simplify the following:
5 + 9 (2 + 4)
2 + 4 = 6:
5 + 9×6
9×6 = 54:
5 + 54
5 + 54 = 59:
Answer: 59
Answer:
See the explanation below.
Step-by-step explanation:
![f(t)=21020\left(1+0.012\right)^t\\\\f(t)=21020\left(1.012\right)^t\\](https://tex.z-dn.net/?f=f%28t%29%3D21020%5Cleft%281%2B0.012%5Cright%29%5Et%5C%5C%5C%5Cf%28t%29%3D21020%5Cleft%281.012%5Cright%29%5Et%5C%5C)
Starting from ![t=2002](https://tex.z-dn.net/?f=t%3D2002)
By putting
we have:
![f(t)=21020\left(1.012\right)^{13}\\\\\approx 24546](https://tex.z-dn.net/?f=f%28t%29%3D21020%5Cleft%281.012%5Cright%29%5E%7B13%7D%5C%5C%5C%5C%5Capprox%2024546)
First evaluate 990 x 37.
990 x 37 = 36630
Test the given numbers to find the pair that adds up to 36630.
Test 297.
The missing pair will be
36630 - 297 = 36333
Will not work
Test 693.
36630 - 693 = 35937
Will not work
Test 2970.
36630 - 2970 = 33660
Will not work
Test 6930
36630 - 6930 = 29700
This works, because 6930 + 29700 = 36630.
Answer: 6930 and 29700.
Answer:
gfhbvofdjge;rldskgrdfpokcver[;kyhbfd[pgktyhtjkvcblerdfhbvpofjewyrh;fblcvjgiohtrfjcfrthgbjvcikafrghfbcvlkftgjrhfbcvlkxasfjghbbgvdcxkjvnerdsklxcnfesjkdfb vnfawjegb nvmbfc xklcfngdcklfgnrtvdfxksjhwedsxcligbvoiesadfbdfiosgbhjffffff
Step-by-step explanation:
y=4/3-x/6
Step-by-step explanation:
6y/6+x/6=8/6
y+x/6=4/3
-x/6 -x/6
y=4/3-x/6